Strategi BUMDes Bintang Muda Jaya Desa Sako Margasari dalam Mengembangkan Unit Usaha Baru Kabupaten Kuantan Singingi - Adianto Adianto; Mayarni Mayarni (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2021)
Kuantan Singingi Regency must also strengthen the BUMDes owned by the village. Based on the data obtained, Kuantan Singingi Regency has a total of 218 villages, of which there are as many as 100 villages that already have BUMDes and 118 villages that do not have BUMDes. From villages that already have BUMDes, one of them is Sako Margasari Village, Logas Tanah Darat District Kuantan Singingi. The reality of BUMDes in Sako Margasari Village is still moving in saving and borrowing activities for the villagers. BUMDes owned by Sako Margasari Village have not been engaged in forming new business units in an effort to strengthen bumdes capital to support the community economy. This research found that the strategy of BUMDes Bintang Muda Jaya Sako Margasari Village in developing new business units through technological innovations in Sako Margasari Village, Logas Tanah Darat District, Kuantan Singingi Regency is still running not maximum. While the factors that hinder the implementation of bumdes strategy Bintang Muda Jaya Sako Margasari Village in developing new business units through technological innovations in the village of Sako Margasari District Logas Tanah Darat Kuantan Singingi regency is the low competence of BUMDes managers, the lack of business capital to open new business units and the lack of partners factor from BUMDes.